Source of Enhancing Mothers’ Role in The Light of Hadiths Sahih al-Bukhari - Norzulaili Mohd Ghazali; Mesbahul Hoque; Mawaddah Abd Manan (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Abstract Islamic interpretation stabilize the mothers as one of the primary individuals directly responsible for managing their children's lives. However, studies have indicated a concerning decline in the institution of the family, which significantly impacts children's well-being. Furthermore, the demands of contemporary careers often lead to the neglect of mothers' parental responsibilities towards their children. Addressing this crucial issue calls for empowering the role of mothers, this study aims to explore the aspects that require attention and improvement from mothers as they fulfill their roles based on the Hadiths of Sahih al-Bukhari. Employing a qualitative research design, the study utilizes inductive thematic analysis to extract valuable insights from the Hadiths. After extracting the hadiths of the mothers' role from Sahih al-Bukhari using words closely related to the word